2019
DOI: 10.1371/journal.pone.0218920
|View full text |Cite
|
Sign up to set email alerts
|

Short-term sleep fragmentation enhances anxiety-related behavior: The role of hormonal alterations

Abstract: Introduction The neuroendocrine background of acute sleep fragmentation in obstructive sleep apnea and sleep fragmentation involvement in psychiatric comorbidities, common in these patients, are still largely unknown. The aim of this study was to determine the effects of short-term experimental sleep fragmentation on anxiety -like behavior and hormonal status in rats. Methods Male rats were adapted to treadmill (ON and OFF mode with belt speed set on 0.02m/s and 0.00m/s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 77 publications
1
16
0
1
Order By: Relevance
“…We have previously shown that sleep deprivation induces anxiety-linked behavior in both humans and animals. On the other hand, there is an association between anxiety and oxidative stress in the brain [ 25 , 33 , 53 55 ]. Present results indicated that there is a correlation between oxidative stress byproducts and anxiety behavior of the rats after sleep fragmentation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that sleep deprivation induces anxiety-linked behavior in both humans and animals. On the other hand, there is an association between anxiety and oxidative stress in the brain [ 25 , 33 , 53 55 ]. Present results indicated that there is a correlation between oxidative stress byproducts and anxiety behavior of the rats after sleep fragmentation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the role of sleep fragmentation in the mediation of anxiety in OSA patients seems to be very rational to hypothesize. Indeed, the models of acute sleep fragmentation recently developed in rodents confirmed an effect on cognition, in particular, memory consolidation, brain excitability, and anxiety-related behaviors [ 22 25 ]. However, we still do not have clear experimental data on the relationship between sleep fragmentation in OSA and anxiety-linked behavior, nor the underlying molecular mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…In line with human studies, experiments in BL6 mice showed that low REMS continuity at baseline was correlated with higher levels of hyperarousal one month after contextual fear conditioning 46 . Moreover, as a proof of principle, experimentally induced sleep fragmentation led to an increase of anxiety-like behavior in rats 74 . Another study found more spontaneous awakenings in more anxious BALBc/J mice than in BL6 www.nature.com/scientificreports/ controls 75 .…”
Section: Insomnia-like Features: Increased Sleep Latency and Awakenings From Rems In The Light Periodmentioning
confidence: 95%
“…It is well established that sleep disturbances have negative effects for mental health (McCoy & Strecker, 2011). In animal models, sleep disturbances induce anxiety‐like behaviors (Grubac et al., 2019; Silva et al., 2004) and depressive‐like behaviors (Gonzalez‐Castañeda et al., 2016; Wang et al, 2017). In this regard, the possible effect of our simulated shift‐work protocol on sleep patterns and its association with the development of depressive and anxiety‐like behaviors as observed in W‐AL rats could not be discarded.…”
Section: Discussionmentioning
confidence: 99%